Extraction and characterization of microfibrillated and nanofibrillated cellulose from office paper waste - Md Hanafiah, Siti Fatimah; Danial, Wan Hazman; Abu Samah, Mohd Armi; Samad, Wan Zurina; Darnis, Deny Susanti; Mohd Salim, Rosliza; Abdul Majid, Zaiton (2018)
The tremendous increased in papermaking and cellulose production, which both sources from wood pulp has resulted in severe exploitation of trees, leading to environmental problems, the deforestation. Besides, the reduction of paper usage is rather not in the horizon. Thus, concerning with the environmental issue, the extraction of cellulose from the paper waste can be an alternative initiative to mitigate the negative impact via reusability of paper waste. In this study, the extraction of cellulose microfibers and nanofibers were achieved using office paper waste as the source material. Alkali and bleaching treatments were employed for the extraction of cellulose fibers followed by controlled-conditions of acid hydrolysis for the isolation of the cellulose nanofibers. The alkali treatment was carried out using various concentrations of 2%, 4%, 8% and 16% of sodium hydroxide (NaOH) solution while the bleaching treatment was carried out using sodium hypochlorite (NaClO) solution. The extraction of nanofibrillated cellulose was achieved using controlled-conditions of acid hydrolysis treatment with various concentrations of 5%, 15%, 30% and 60% sulphuric acid (H2SO4). Structural and functional groups analysis was analyzed using Attenuated Total Reflection Fourier Transform Infra-Red (ATR-FTIR) while imaging and morphological analysis was examined using optical microscopy and transmission electron microscopy (TEM). FTIR analysis indicated the lignin, ink, fillers and other components were removed after alkali and bleaching treatments. Imaging analysis using optical microscope showed a fibrous and rod-like structure of the extracted cellulose while TEM images showed that the size of the cellulose extracted range from micro to nano size down to ~20-30 nm depending on the concentration of acid used. The extraction of either microfibrillated or nanofibrillated cellulose from office paper waste in this work might paves the way toward alternative reuse of office paper waste in cellulose materials production and application